Biosurfactant Production and Growth Kinetics Studies of the Waste Canola Oil-Degrading Bacterium Rhodococcus erythropolis AQ5-07 from Antarctica ... : دراسات حركية إنتاج المواد الخافضة للتوتر السطحي ونمو بكتيريا نفايات الكانولا المتحللة للزيت Rhodococcus erythropolis AQ5 -07 من القارة القطبية الجنوبية ... - Salihu Ibrahim; Khalilah Abdul Khalil; Khadijah Nabilah Mohd Zahri; Claudio Gómez-Fuentes; Peter Convey; Azham Zulkharnain; Suriana Sabri; Siti Aisyah Alias; Gerardo González-Rocha; Siti Aqlima Ahmad (OpenAlex, 2020)
With the progressive increase in human activities in the Antarctic region, the possibility of domestic oil spillage also increases. Developing means for the removal of oils, such as canola oil, from the environment and waste "grey" water using biological approaches is therefore desirable, since the thermal process of oil degradation is expensive and ineffective. Thus, in this study an indigenous cold-adapted Antarctic soil bacterium, Rhodococcus erythropolis strain AQ5-07, was screened for biosurfactant production ability using the multiple approaches of blood haemolysis, surface tension, emulsification index, oil spreading, drop collapse and "MATH" assay for cellular hydrophobicity. The growth kinetics of the bacterium containing different canola oil concentration was studied. The strain showed β-haemolysis on blood agar with a high emulsification index and low surface tension value of 91.5% and 25.14 mN/m, respectively. Of the models tested, the Haldane model provided the best description of the growth ... : مع الزيادة التدريجية في الأنشطة البشرية في منطقة القطب الجنوبي، تزداد أيضًا احتمالية تسرب النفط المحلي. لذلك فإن تطوير وسائل لإزالة الزيوت، مثل زيت الكانولا، من البيئة ونفايات المياه "الرمادية" باستخدام الأساليب البيولوجية أمر مرغوب فيه، لأن العملية الحرارية لتدهور الزيت مكلفة وغير فعالة. وهكذا، في هذه الدراسة، تم فحص بكتيريا تربة أنتاركتيكية أصلية متكيفة مع البرد، وهي سلالة Rhodococcus erythropolis AQ5 -07، بحثًا عن قدرة إنتاج المواد الخافضة للتوتر الحيوي باستخدام الأساليب المتعددة لانحلال الدم والتوتر السطحي ومؤشر الاستحلاب وانتشار الزيت وانهيار السقوط وفحص "الرياضيات" لكراهية الماء الخلوية. تمت دراسة حركية نمو البكتيريا التي تحتوي على تركيز مختلف لزيت الكانولا. أظهرت السلالة انحلال الدم بيتا على آجار الدم مع مؤشر استحلاب مرتفع وقيمة توتر سطحي منخفضة تبلغ 91.5 ٪ و 25.14 مللي نيوتن/متر، على التوالي. من بين النماذج التي تم اختبارها، قدم نموذج هالدين أفضل وصف لحركية النمو، على الرغم من أن العديد من النماذج كانت متشابهة في الأداء. كانت المعلمات التي تم الحصول عليها من النمذجة هي الحد الأقصى لمعدل النمو النوعي ...